The Process and Affordances of Platform-Specific Social Media Disconnection - Ramona-Riin Dremljuga (Studies of Transition States and Societies, 2018)
This article examines millennials’ experience of platform-specific disconnection, focusing on the ambiguous intersection of engagement and disengagement with social media. Drawing on 16 semi-structured interviews with (non)users who have quit specific social media platforms while remaining users on other platforms, this study addresses a specific practice of social media disengagement as a phenomenon, regardless of the (non)users’ demographics. As a result, the study introduces phases leading up to platform-specific disconnection, which can extend to, or derive from, other practices of media rejection and resistance. These different stages refer to the technical and social affordances that influence users in their decision to (dis)engage with specific platforms, revealing a bias between the perception of the phenomenon and the lived experience of the disconnected. By visualizing the process of platform-specific disengagement, this paper provides novel insight into media resistance and non-use, and challenges the misconception of disconnecting in the digital age.